2017
DOI: 10.5941/myco.2017.45.2.101
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genes Related to Fungicide Resistance inFusarium fujikuroi

Abstract: We identified two genes related to fungicide resistance in Fusarium fujikuroi through random mutagenesis. Targeted gene deletions showed that survival factor 1 deletion resulted in higher sensitivity to fungicides, while deletion of the gene encoding F-box/WD-repeat protein increased resistance, suggesting that the genes affect fungicide resistance in different ways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…However, the link between F box or WD repeat protein and survival factor 1 with the sensitivity of F. fujikuroi to prochloraz fungicide was found. The resistance to prochloraz was reduced due to the disruption of genes survival factor 1 whereas, the disruption of genes in F box or WD repeat protein enhanced resistance in F. fujikuroi to prochloraz (Choi et al, 2017 ).…”
Section: Control Methodsmentioning
confidence: 99%
“…However, the link between F box or WD repeat protein and survival factor 1 with the sensitivity of F. fujikuroi to prochloraz fungicide was found. The resistance to prochloraz was reduced due to the disruption of genes survival factor 1 whereas, the disruption of genes in F box or WD repeat protein enhanced resistance in F. fujikuroi to prochloraz (Choi et al, 2017 ).…”
Section: Control Methodsmentioning
confidence: 99%
“…Whereas, Zhang et al [44] reported that the S312T mutation in CYP51B and overexpression of the CYP51A/CYP51B genes caused prochloraz resistance in Chinese F. fujikuroi. Choi et al [56] found an association between survival factor 1 and F-box/WD-repeat protein with prochloraz sensitivity of F. fujikuroi. Gene disruption of survival factor 1 decreased prochloraz resistance while gene disruption of F-box/WD-repeat protein increased prochloraz resistance [56].…”
Section: Sterol Demethylase Inhibitorsmentioning
confidence: 99%
“…Choi et al [56] found an association between survival factor 1 and F-box/WD-repeat protein with prochloraz sensitivity of F. fujikuroi. Gene disruption of survival factor 1 decreased prochloraz resistance while gene disruption of F-box/WD-repeat protein increased prochloraz resistance [56].…”
Section: Sterol Demethylase Inhibitorsmentioning
confidence: 99%
“…(Soković et al, 2013). Continued use of fungicides causes the emergence of resistant forms in populations of phytopathogens: resistance of Fusarium to prochloraz, tebuconazole and benomyl (Choi et al, 2017); cross-resistance of Alternaria alternata to mancozeb and difenoconazole (Yang et al, 2019). People require natural foods without dangerous substances to improve their health.…”
Section: Introductionmentioning
confidence: 99%